The treatment of equivalent relations in English-Kwanyama Dictionary (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper investigates the treatment of equivalent relations in English-Kwanyama Dictionary (EKD) by G. W. R. Tobias and B. H. C Turvey compiled in 1954. For any bilingual dictionary to satisfy the needs of the target users, it should treat the equivalent relations effectively (Gouws, 2002; Gouws & Prinsloo, 2005 & Svensén, 2009). Although EKD was compiled 65 years ago, it seems no comprehensive study has been conducted to evaluate its effectiveness. Hence thispaper is an attempt to evaluate its treatment and the effectiveness of equivalent relations. The paper is couched on the text theory of Herbert Ernst Wiegand which deals with dictionary textual structures, function theory developed by Sven Tarp, and Henning Bergenholtz that focuses on dictionary functions as well as the user needs. In addition, lexicographic theory of communication developed by Beyer (2014) is employed to analyse EKD purposes. The findings reveal that full equivalence is treated well in EKD, but partial equivalence and zero equivalence have not been presented effectively in EKD. This paper recommends that EKD be revised extensively to present all types of equivalent relations adequately.
Keywords: lexicographic theory; English-Kwanyama Dictionary; text theory; function theory developed